Case Report: Anaesthetic management in a canine patient with severe atrioventricular septal defect and pulmonary hypertension undergoing non-cardiac surgery - Nicol, Claire; Kriström, Karin; Bettembourg, Vanessa (Frontiers in Veterinary Science, 2026)
IntroductionA 9-year-old, 6.8-kg intact male Petit Brabançon with a congenital partial atrioventricular septal defect (AVSD) presented for dental extractions. Pre-anaesthetic echocardiographic assessment revealed a large ostium primum atrial septal defect with bidirectional interatrial shunting, severe right atrial and ventricular enlargement, abnormal atrioventricular valves with severe tricuspid regurgitation, mild relative pulmonic stenosis, and moderate pulmonary hypertension (PH). Anaesthetic goals were to minimize increases in pulmonary vascular resistance (PVR), preserve right ventricular perfusion and cardiac output (CO), and avoid alterations in intracardiac shunt dynamics that could promote right-to-left shunting. Premedication consisted of methadone [0.2 mg/kg intramuscularly (IM)], lidocaine (1 mg/kg intravenously (IV)) and midazolam (0.3 mg/kg IV). Continuous infusions of lidocaine (30–50 μg/kg/min) and remifentanil (10–30 μg/kg/h) were used as inhalant minimum alveolar concentration (MAC)-sparing analgesic adjuncts. Anaesthesia was induced with ketamine (1 mg/kg IV) and propofol (2 mg/kg IV) and maintained with sevoflurane in oxygen and air. Controlled ventilation targeted normocapnia and the fraction of inspired oxygen (FiO₂) was titrated to maintain pulse oximeter (SpO₂) values above 95%, while avoiding unnecessary hyperoxia. A norepinephrine infusion (0.2–0.4 μg/kg/min) supported mean arterial pressure (MAP) > 65 mmHg. Regional dental nerve blocks supplemented analgesia. Fourteen teeth were extracted during a 64-min anaesthetic. Recovery was complicated by transient hypoxemia attributed to upper airway obstruction, resolving with oxygen supplementation and nebulized adrenaline.OutcomeNo arrhythmias or sustained right-to-left shunting occurred. The dog was discharged the same day and returned to normal activity. Survival after the procedure was 14 months before euthanasia for acute respiratory decompensation.Clinical relevanceThis report highlights practical, physiology-guided strategies to conduct anaesthesia in non-cardiac procedures in dogs with severe AVSD and PH, in hospital settings without advanced equipment such as intra-operative transesophageal echocardiography or direct CO measurements. It also serves as a reminder not to let the anaesthetic risk in patients with severe cardiac disease be the reason for refraining from quality of life improving dental procedures.